Communicating Science, Technology, and Environmental Issues: A Case Study of an Intercultural Learning Experience - van Kempen, Anke; Kristiansen, Silje; Feldpausch-Parker, Andrea M. (Frontiers in Communication, 2022)
This science communication case study analyzes an online international co-taught course where students practiced blog article conceptualization and production covering a wide variety of science and technology related issues. Students had an international experience during the COVID-19 pandemic, and gained experience in communicating science and technology to intercultural audiences. Through student article reviews, course evaluations and project reflections students demonstrated an adoption of new science communication skills and some key examples of changing perspective on issues such as environment and technology. They also enjoyed the opportunity to learn about new cultures, reflect on their own, and bond over life experiences.